2007
DOI: 10.1002/hed.20574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of HER‐2/neu expression on squamous head and neck carcinomas

Abstract: HER2/neu overexpression and its relationship with survival suggest that new therapeutic approaches targeting epidermal growth factor receptor (EGFR) family receptors could provide a new way of treating HNSCC patients with HER2/neu-positive neoplastic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 42 publications
14
59
0
Order By: Relevance
“…6B). Notably, HER-2 has been suggested as an oncogene/tumor marker for OSCC in previous studies (25,26). In our mouse tumor study, we also identified significant expression levels of HER-2 in mouse oral tumors.…”
Section: Resultssupporting
confidence: 75%
“…6B). Notably, HER-2 has been suggested as an oncogene/tumor marker for OSCC in previous studies (25,26). In our mouse tumor study, we also identified significant expression levels of HER-2 in mouse oral tumors.…”
Section: Resultssupporting
confidence: 75%
“…13,14 Head and neck cancers have been associated with EGFR family proteins and signal transduction molecules downstream. [15][16][17][18][19][20] Hence it is a relevant to use anti-EGFR based therapy in addition to the standard of care prevalent. 5,13,21 Overall in this study, the mR3 antibody showed a similar recognition profile to the EGFR Santa Cruz antibody, but they were not identical (Fig.…”
mentioning
confidence: 99%
“…A marked Her-2/neu membranous overexpression was already found in other endocrine tumors including papillary thyroid [36], pheochromocytomas [37], and small cell lung carcinomas [38] as well as in nonendocrine tumors including those of esophagus [8], stomach [8,39], breast [40], head and neck [41], colon [8,42], and ovary [43]. In all these studies, HER-2/neu overexpression inversely correlates with survival and directly with increased invasiveness and aggressive growth, representing an important prognostic factor for many human tumors.…”
Section: Discussionmentioning
confidence: 99%